ANALISIS EFEKTIVITAS REKAM MEDIS ELEKTRONIK BERBASIS WEB UNTUK MENGURANGI KETERLAMBATAN PENYEDIAAN REKAM MEDIS PASIEN RAWAT JALAN DI RUMAH SAKIT BALIMED KOTA DENPASAR - Agus Donny Susanto; I Wayan Widi Karsana; Putu Ayu Agustini Arfaningsih (program studi Rekam Medis dan Infomasi Kesehatan ITSK RS dr Soepraoen Malang, 2023)
BaliMed Hospital Denpasar City has an SOP for providing outpatient medical records, which is a maximum of 10 minutes with an average patient visit of 12,749 per month. However, there were many delays in the provision of medical records that were not in accordance with the rules for a total of 68 out of 100 documents in the preliminary study. The purpose of this study was to analyze the incidence of delays in the provision of outpatient medical records by providing alternative solutions to Web-based Electronic Medical Record information systems. The development of this system uses the waterfall model or more popularly known as the System Development Life Cycle. The analysis was carried out by carrying out several tests, namely usability and intervention, both of which were to determine the effectiveness of the Web-based Electronic Medical Record information system for the provision of medical records for outpatients at the BaliMed hospital. The results of the usability test by calculating the questionnaire instrument obtained a result of 82.62% and categorized as very good or in other words that the Web-based Electronic Medical Record information system implemented at the BaliMed hospital can be easily used by officers as a research sample. The intervention test used a paired sample t-test and obtained a sig. (2-tailed) of 0.000 <0.05, which explains the influence and effectiveness of the use of the Electronic Medical Record information system on the provision of outpatient medical records.